SG
chevron_right
Secondary 1
chevron_right
Number and Algebra

Factorize using a common factor

Replies
3

Mr. T

we can first combine the terms 10x and -14 to get 10x - 14 = 2(5x - 7). Then, we can substitute this expression into F:
F = (5x-7)(2x+1) + 2(5x - 7)

4 days ago

Mr. T

Now, we can see that (5x - 7) is a common factor of the two terms, so we can factor it out:
F = (5x - 7)(2x + 1 + 2)

4 days ago

Mr. T

Simplifying the expression inside the parentheses, we get:
F = (5x - 7)(2x + 3)
Therefore, the fully factorized form of the expression F is:
F = (5x - 7)(2x + 3)

4 days ago

Shann

Asked 3 weeks ago

SG
chevron_right
Primary 4
chevron_right
Number and Algebra